BAHTSUL MASAIL’S CRITICAL REVIEW OF FAKE ORDER ONLINE ON THE DIGITAL SHOPEE LIVE PLATFORM - Yuni K, Kusnul Ciptanila; Musfiroh, Anita; Dardiri, Masyhudan; Nur Efendi, Mohamad; Santoso, Lukman (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2024)
Selling online through various digital platforms is an alternative business. Many successful people have made huge profits from it. However, fraud, deception, the spread of fake accounts, and counterfeit transactions often occur and harm many people. This research explores the practice of buying and selling with bogus and counterfeit accounts on digital platforms. This research is qualitative research with a case study approach. Bahtsul Masail is the highest forum that discusses actual community problems for which no evidence or legal solution has been found. The answer to this problem was sought and taken from Politikul Mu'tabaroh. This research resulted in the finding that the law of asking buyers for postage in the above cases is not permitted because (1) the postage is not used correctly, instead as an additional income; (2) if the buyer knows this reality, it is inevitable that he will not be willing to pay the postage to the seller. It is not permitted because it is fraud. This study provides clarity on deviant buying and selling practices on digital platforms.